King Arthur [videorecording (DVD)] : legend of the sword - Ritchie, Guy; Hunnam, Charlie, 1980-; Berges-Frisbey, Astrid; Law, Jude, 1972-; Bana, Eric (Village Roadshow Pictures : Warner Home Video, 2017)
Robbed of his birthright, Arthur comes up the hard way in the back alleys of the city. Once he pulls the sword from the stone, he is forced to acknowledge his true legacy, whether he likes it or not.